BRANDING BRAWIJAYA EDUPARK SEBAGAI WISATA EDUKASI DI MALANG - Asfira Rachmad Rinata (Universitas Tribhuwana Tunggadewi, 2021)
Brawijaya Edupark is one of the tourist destinations in Malang, East Java, which was previously known as Taman Wisata Senaputra. The change of the name Senaputra Tourism Park to Brawijaya Edupark is a new thing for the people of Malang City. The purpose of this research is to describe the image of Brawijaya Edupark educational tourism after the name change from Taman Wisata Senaputra. This study uses a qualitative method. The data collection process was carried out by means of interview, documentation, and observation. The result showed that the branding carried out by Brawijaya Edupark was to raise the concept of recreational tourism and early childhood education,